Analisis Perubahan Kerapatan Vegetasi Penutup Lahan dengan Metode Indeks Vegetasi NDVI (Studi Kasus di Kawasan Hutan Rakyat Kabupaten Gunung Kidul) - Husni, Muhamad Fakhri; Wahyudiono, Sugeng; Suhartati, Tatik (Jurnal Wana Tropika, 2024)
This study aims to analyze changes in vegetation density in Gunungkidul Regency using the NDVI (Normalized Difference Vegetation Index) method based on Landsat 8 satellite imagery. The research focuses on evaluating the condition of teak forest vegetation density in Gunungkidul Regency in 2013 and 2023, with the goal of identifying land cover changes and providing an overview of the forest ecosystem conditions in the area. The methods used in this research include processing satellite imagery with spatial analysis techniques using GIS (Geographic Information System) software. NDVI data was analyzed to measure vegetation density for both time periods, classifying land cover into several categories: non-vegetated land, very low vegetation, low vegetation, and moderate vegetation. The analysis results were compared to identify trends in changes over the ten-year period. The findings indicate that there has been a change in vegetation density in Gunungkidul Regency, with a decrease in the area of low vegetation from 126,747.87 hectares in 2013 to 118,972.88 hectares in 2023 (6,13%). An increase in non-vegetated land was also recorded, rising from 513.47 hectares to 1,107.76 hectares during the same period (113,24%). Although there were some improvements in vegetation density, the increase in non-vegetated land indicates challenges in land management in the region.